Longitudinal Plasmonic Detection of Glucose Using Gold Nanorods - Ching-An Peng; Sushil Pachpinde (Nanomaterials and Nanotechnology, 2014)
Gold nanorod-based affinity sensors were developed utilizing concanavalin-A/dextran/glucose chemistry to detect glucose. The gold nanorods, synthesized using the seed-mediated method, were first coated with dextran sulfate. The dextran sulfate coating changed the local refractive index, which was observed as a red shift in the longitudinal plasmon band. After the addition of 8 μM concanavalin-A, gold nanorod aggregates were formed as shown by TEM analysis. The corresponding UV-Vis spectrum peak wavelength showed a red shift from 701 nm of dextran sulfate coated gold nanorods to 718 nm of concanavalin-A promoted gold nanorod aggregates. The gold nanorod aggregates were dissociated when 12 mM glucose was introduced, as illustrated by TEM images. The longitudinal plasmon resonance of the UV-Vis spectrum also showed a blue shift from 718 nm of dextran sulfate-coated gold nanorods associated by concanavalin-A to 714 nm of dissociated dextran sulfate-coated gold nanorods. The degree of the spectrum peak wavelength shift of the dextran sulfate-coated gold nanorods associated by concanavalin-A can be modulated using glucose ranging from 1 to 30 mM.